Transorbital endoscopic-assisted management of intraorbital lesions: Experience of 11 cases. Issue 3 (May 2023) - Ben Cnaan, Ran; Barequet, Dana; Abumanhal, Muhammad; Leibovitch, Igal; Abergel, Avraham
Purpose: To present our experience in the management of selected extraconal orbital roof lesions utilizing the transorbital endoscopic approach. Methods: A retrospective case series of patients who underwent transorbital endoscopic orbital surgery in a single medical center between 2015 to 2020. Results: Eleven patients underwent transorbital endoscope assisted surgery for various indications. The mean age at surgery was 31.9 years (range, 6–73 years). Mean follow-up time was 18 months (range, 1–30). The aim of surgery was curative in 10 cases and diagnostic in one patient. Adequate specimen for tissue diagnosis was obtained from all patients. In 8 patients the procedure was completed through a superior eyelid crease incision, and in three patients a combined approach including functional endoscopic sinus surgery was used for achieving complete excision. None of the patients required conversion to an external wider orbital procedure. Intraoperative complication included cerebrospinal fluid leak in one case, which was addressed immediately; and postoperative complications included one case of pre-septal orbital cellulitis treated by intravenous antibiotics with complete resolution. Conclusion: Endoscopic-assisted transorbital approach enabled safe removal of selected lesions involving the orbital roof and provides an effective and less invasive alternative to a traditional frontal craniotomy or lateral orbitotomy.